Nipah virus in India: past, present and future - M. S., Prarthana (International Journal Of Community Medicine And Public Health, 2018)
Nipah virus (NiV) is one of the emerging highly pathogenic virus. Like Ebola and Zika viruses, NiV too is threatening the integrity of the mankind. The family Paramyxoviruses has been traditionally associated with a group of viruses with narrow host range and typically causes outbreaks with low mortality rates. But with the emergence of highly pathogenic Hendra virus and closely related NiV, they have evolved as a cause of fatal encephalitis across broad range of vertebrate species including humans. The natural reservoir of NiV is Pteropus bat, which is apparently distributed all over the South East Asia. The bat population from North East to North West states in India have NiV antibodies which mean there is active NiV infection among Indian bats. As NiV is associated with high morbidity and mortality they pose a risk from natural outbreaks, laboratory accidents or deliberate misuse. The development of effective prevention and treatment strategies is very crucial. Preparedness, surveillance, constant vigil needs to be carried out continuously in the country. The present outbreak in India after nearly eleven years with a high case fatality rate indicate that there is a total lack of health care systems preparedness and surveillance strategy. The anthropogenic and environmental changes occurring due to rapid urbanization and massive deforestation has made India now even more vulnerable for such recurrent outbreaks. This review highlights the changing trend of the NiV outbreaks in the past and the current outbreak in India.